2016
DOI: 10.1074/jbc.m115.686121
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel Homolog 1 Inhibits Insect Metamorphosis via Direct Transcriptional Repression of Broad-Complex, a Pupal Specifier Gene

Abstract: The Broad-Complex gene (BR-C) encodes transcription factors that dictate larval-pupal metamorphosis in insects. The expression of BR-C is induced by molting hormone (20-hydroxyecdysone (20E)), and this induction is repressed by juvenile hormone (JH), which exists during the premature larval stage. Krüppel homolog 1 gene (Kr-h1) has been known as a JH-early inducible gene responsible for repression of metamorphosis; however, the functional relationship between Kr-h1 and repression of BR-C has remained unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
124
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 45 publications
3
124
1
2
Order By: Relevance
“…The pupal specifier BR-C is differentially regulated by Kr-h1 in holometabolous insects; it is induced in response to JHmediated Kr-h1 expression at the prepupal and pupal stages, whereas Kr-h1 represses BR-C during the larval stage (17,18,24,25,28,36). The transcription factor CSL [CBF1/Su(H)/Lag-1] recruits a corepressor complex in the absence of Notch signaling to repress its target genes (51); however, Notch signaling converts the CSL repressor complex to an activator complex, resulting in transcriptional activation of the target genes (51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pupal specifier BR-C is differentially regulated by Kr-h1 in holometabolous insects; it is induced in response to JHmediated Kr-h1 expression at the prepupal and pupal stages, whereas Kr-h1 represses BR-C during the larval stage (17,18,24,25,28,36). The transcription factor CSL [CBF1/Su(H)/Lag-1] recruits a corepressor complex in the absence of Notch signaling to repress its target genes (51); however, Notch signaling converts the CSL repressor complex to an activator complex, resulting in transcriptional activation of the target genes (51).…”
Section: Discussionmentioning
confidence: 99%
“…In Lepidoptera, JH was shown to repress 20E-dependent induction of BR-C in the larval epidermis (26,27). We have found that Kr-h1 directly binds to a site within the BR-C promoter and represses 20E-dependent BR-C activation (28). Through these molecular actions, JH prevents immature larvae from undergoing precocious larval-pupal transition.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In a simplified model, a lepidopteran progresses through a larvato-larva molt when JH is present and a larva-to-pupa metamorphosis when JH is absent at the final molting stage. It has been hypothesized that JH modulates the action of ecdysteroid-molting hormones, but the detailed mechanisms of the modulation are still unclear (Jindra et al 2013;Urena et al 2014;Kayukawa et al 2016). There is some evidence that JH has an effect on larval pigmentation.…”
Section: Juvenile Hormone Directly Regulates Larval Color Pattern Switchmentioning
confidence: 99%
“…One obvious candidate is the zinc-finger protein Kr-h1, which plays a critical role as a JHinduced repressor of insect metamorphosis (11,14). Interestingly, a recently published paper shows that Kr-h1 indeed acts via direct DNA binding to repress transcription of the Broad-Complex gene (15), which is absolutely necessary to initiate metamorphosis (larva-to-pupa transition) in holometabolous insects (11). Whether the transcriptional repressor Kr-h1 also regulates genes important for the mosquito PE development remains to be investigated.…”
mentioning
confidence: 99%